An edition of a selection of poems by John Randal Bradburne - Hacksley, Helen Elizabeth (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2006)
This thesis examines the life and work of John Randal Bradburne (1921-1979), poet, mystic, musician, cenobite, sometime soldier, pilgrim and wanderer. His religious experiences, particularly, gave rise to a vast corpus of verse, virtually all of it as yet unpublished. This study provides a brief overview of his life, and a critical and textual introduction to a sample selection of poems entitled Bradburne 's Assays. The biography has been compiled from published and unpublished sources, as well as from personal interviews and correspondence with Bradburne's friends, relatives and associates in South Africa, Zimbabwe and the United Kingdom. Chief among these are two unpublished biographies by Judith, Countess of List owe I. Bradburne's extant corpus consists of over five thousand titled pieces of verse, ranging from brieflyrics to verses hundreds of pages long. The forty-seven poems comprising Bradburne 's Assays, published here for the first time, were selected and arranged by Bradburne himself in a single sequence. A unique collection in his corpus, they are unified by their common sonnet form and their contemplative approach to secular and religious experiences. An accurate reading text of this set of poems, transcribed from Bradburne's typescripts, currently held at Holyhead in Wales, is provided. These typescripts have been electronically scanned and are presented in the Appendix. Editorial intrusion, which has been kept to a minimum, is recorded in the critical apparatus beneath the text of the poems. Since all the poems in this ed ition are presented here for the first time, each is accompanied by detailed commentary on their form and content. Where necessary, interpretations of obscure passages have been suggested. A general index to the Introduction and Commentary is supplied, along with indexes of first lines and titles of the poems. It is hoped that this thesis will stimulate further study of the life and work of a unique and intriguing figure.
Keywords: Bradburne, John, -1979; Bradburne, John, -1979 -- Criticism and interpretation; Poets, South African -- 20th century -- Biography